(untitled) (Research, Society and Development, 2020)
The present work approaches some legislative changes, as well as regulations of the National Council of Justice that encourage the resolution of conflicts by alternative means, such as conciliation and mediation, through extrajudicial means. The monopoly of the Judiciary Power for the solution of conflicts no longer attends to excessive procedural demand, making the adjudication a viable means to attend to the social anxieties. The realization of conciliation and mediation by the extrajudicial forum maintains the principle of access to justice, in a fast and economic way. However, in addition to legislative changes, it is necessary to change the behavior of the interested parties, so that the extrajudicial route has real applicability and satisfactory effects.